Evaluation of Biology Learning Assessment Instruments on the Excretory System Concept for Grade VIII Junior High School Students - Sastri Nilawati; Hendro Prasetyono (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study aims to evaluate the quality of Biology learning assessment instruments on the excretory system material for Grade VIII junior high school students based on their alignment with Learning Outcomes (Capaian Pembelajaran, CP), Learning Objectives (Tujuan Pembelajaran, TP), item indicators, cognitive domains, and item quality. This study employed an evaluative descriptive approach using a document evaluation model. The data were obtained through an analysis of 30 test items used by teachers in the excretory system material. The evaluation instrument was a review sheet covering aspects of substance, construction, language, alignment with CP and TP, and the distribution of cognitive levels based on the Revised Bloom’s Taxonomy. The results showed that most of the items were aligned with CP and TP; however, they were still dominated by lower cognitive domains (C1–C2). The alignment of the indicators reached 86.67%, whereas the proportion of HOTS items remained low. These findings indicate the need to develop assessment instruments that are more oriented toward higher-order thinking skills.